Corona Crisis: Transformative Recession - Christian Hutter; Enzo Weber (Wirtschaftsdienst)
Abstract With the Corona crisis, unemployment is increasing in Germany despite all the countermeasures taken. In previous recessions, unemployment of the low-skilled in particular has become entrenched. Today, it is becoming apparent that technological change is also affecting medium-skilled workers in particular. In order to avoid consolidation, it is important to promote new hires, support qualification and enable vocational reorientation.